Development of a Prototype Website For the Lake Toba Authority Planning Agency Based on the Ictrt Model (Information, Communication, Transaction, Relationship, and Technical-Merit) - Nency Ayu Wandira; Hasan Sobirin; Wahyu Dito Galih Indharto; Ade Subardi Darus; Mosanda Tampubolon; Elisabeth Ayu Ningsih Hutabarat (Politeknik Pariwisata Makassar, 2024)
The purpose of this study was to determine the development of a prototype of the Lake Toba Planning Authority website based on the ICTRT model. This research method is descriptive qualitative. The location of the study is on the BPODT website, Toba Caldera, North Sumatra Province. The research period is June-July 2024. The data sources in this study use primary and secondary data. Primary data was obtained from observations on the BPODT website link. Secondary data was obtained from books, journals, and previous research. Data collection techniques in this study were observation and literature review. The data analysis technique in this study used the ICTRT model which was then carried out by data reduction, data presentation, and drawing conclusions. The results of the study stated that the development of the BPODT website was carried out to make it easier for users to make the website user friendly. The development of the BPODT website was carried out in the information and communication dimensions such as photo galleries, creating travel tips, creating destination facts, and adding information via email. The development of this website was carried out as a short link that makes it easy for users to get information quickly and accurately.